2023
DOI: 10.1109/jstars.2023.3308045
|View full text |Cite
|
Sign up to set email alerts
|

Attribution of Urban Diurnal Thermal Environmental Change: Importance of Global–Local Effects

Wenbo Yu,
Jun Yang,
Nan Cong
et al.

Abstract: Global climate change is causing various negative impacts on urban ecosystems and energy systems. To effectively mitigate and adapt to these changes, it is important to understand the contributions of background climate and local effects to urban thermal environment variation. This study utilized the empirical orthogonal function (EOF) approach to deconstruct long-term MODIS land surface temperature (LST) datasets to obtain the main features of change in daytime and nighttime thermal environments. Local bivari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2024
2024
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 72 publications
0
3
1
Order By: Relevance
“…Third, the shape and size of built-up areas and surrounding green patches also have impacts on the LST of different built-up age cohorts. Urban areas exhibit a variable LST pattern that can be linked to albedo variations [85][86][87]; the increase in building density and floor area ratio will also cause LST to rise with urban construction [61,[88][89][90]. In contrast to previous studies, our results show that landscape plays a leading role in determining the LST pattern among built-up age cohorts (Figure 5).…”
Section: Temporal Stability Of the Spatial Pattern Of Lstcontrasting
confidence: 77%
“…Third, the shape and size of built-up areas and surrounding green patches also have impacts on the LST of different built-up age cohorts. Urban areas exhibit a variable LST pattern that can be linked to albedo variations [85][86][87]; the increase in building density and floor area ratio will also cause LST to rise with urban construction [61,[88][89][90]. In contrast to previous studies, our results show that landscape plays a leading role in determining the LST pattern among built-up age cohorts (Figure 5).…”
Section: Temporal Stability Of the Spatial Pattern Of Lstcontrasting
confidence: 77%
“…Research concerning urban morphology-LST relationships has predominantly centered on their correlation. [37], [25], [38], [39]. Guo et al (2020) investigated indices such as landscape patterns, the proportion of construction land (PCL), the proportion of woodland and grass (PWG), and the 2 > IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing < normalized difference built-up index (NDBI), identifying a strong correlation between NDBI and LST.…”
Section: Introductionmentioning
confidence: 99%
“…By moderating energy and water exchanges between land and the atmosphere, urban trees exert considerable influence on the climate system, operating at both local and regional scales [9], [10]. Extensive research conducted at local and urban scales has consistently demonstrated the diverse environmental benefits of urban trees, including the mitigation of microclimatic conditions [5], [11], [12], [13], reduction of heat island intensity [2], [6], [14], alleviation of air pollution [1], [3], and preservation of biodiversity [15], [16]. Moreover, urban trees have been widely acknowledged for their protective effects on human health and mental well-being, attributed to their facilitation of physical activity, support for social interaction, promotion of community awareness, and stress alleviation capabilities [1], [8], [17], [18].…”
Section: Introductionmentioning
confidence: 99%